Slang Formation and Usage in VTuber Communities on Reddit - Byvan Quai Alkana; Bagaskara Wijayakusuma; Pratista Shafa Brillian (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This research aims to analyze VTuber community slang on Reddit utilizing digital ethnography. Specifically, this research aims to examine the formation and use of slang in VTuber communities. This research employs a qualitative descriptive approach and purposive sampling. The data were collected from posts and comments on two subreddits, r/kurosanji and r/VirtualYoutubers, in text form. The data analysis was conducted utilizing Allan and Burridge’s slang theory. The researcher finds that the VTubers community utilized four categories of slang: acronym, clipping, flippant, and fresh and creative. Clipping, fresh, and creative are the most commonly used VTuber community slang, while acronym and flippant are the least used. The slang was used to create a sense of identity among VTubers. It is also used to label and offend members of VTuber subreddits and other groups. It also serves as a quick communication between members. This research contributes to the development of digital ethnography and further research regarding the VTuber community and its slang.